2023
DOI: 10.1002/iid3.1043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of KLF9 in airway inflammation in chronic obstructive pulmonary

Peijie Gu,
Zhen Wang,
Xin Yu
et al.

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is an airway‐associated lung disorder, resulting in airway inflammation. This article aimed to explore the role of the krüppel‐like factor 9 (KLF9)/microRNA (miR)‐494‐3p/phosphatase and tensin homolog (PTEN) axis in airway inflammation and pave a theoretical foundation for the treatment of COPD.MethodsThe COPD mouse model was established by exposure to cigarette smoke, followed by measurements of total cells, neutrophils, macrophages, and hematoxylin and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It has been reported that dysregulation of antioxidant genes and ROS amplification occur due to suppression of the antioxidant gene by transcription factor Klf9 (Kruppel-like factor) [42][43][44][45], resulting in a sustained increase in ROS production and activation of the Nlrp3 inflammasome pathway. The transcription factor Klf9 (Kruppel-like factor 9) transmodulates genes with a single GC box or repeated GC boxes present in the proximal promoter region of genes [46,47]. Studies have shown the involvement of Klf9 in the regulation of a variety of biological activities, such as cell proliferation, DNA damage, apoptosis and the differentiation of various cell types [45,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dysregulation of antioxidant genes and ROS amplification occur due to suppression of the antioxidant gene by transcription factor Klf9 (Kruppel-like factor) [42][43][44][45], resulting in a sustained increase in ROS production and activation of the Nlrp3 inflammasome pathway. The transcription factor Klf9 (Kruppel-like factor 9) transmodulates genes with a single GC box or repeated GC boxes present in the proximal promoter region of genes [46,47]. Studies have shown the involvement of Klf9 in the regulation of a variety of biological activities, such as cell proliferation, DNA damage, apoptosis and the differentiation of various cell types [45,48,49].…”
Section: Introductionmentioning
confidence: 99%